Emergence of carbapenem-resistant Enterobacteriaceae isolated from patients in a university hospital in Saudi Arabia. Epidemiology, clinical profiles and outcomes - Fawzia E. Alotaibi; Elham E. Bukhari; Maha M. Al-Mohizea; Taghreed Hafiz; Eman B. Essa; Yasmeen I. AlTokhais (Elsevier, 2017)
Carbapenemase-producing Enterobacteriaceae have been steadily spreading worldwide during the last decade. Nine patients were identified prospectively and were followed during their hospitalization course to identify the epidemiology, clinical profiles and outcomes. These patients had one or more cultures positive for a CRE isolate, contributing to a total of eleven positive cultures from various sites without including duplicates of isolates obtained from the same site. Isolates from these patients included five Klebseilla pneumoniae, three Escherichia coli, and one Enterobacter aerogenes. Five isolates were grown from blood cultures, three from wound cultures, one from urine cultures, one from respiratory cultures and one from an abscess collection. Five survived the hospital course. The other five patients died due to severe sepsis, septic shock or multi-organ failure. Of the nine isolates of CRE identified for which molecular analysis were available, four K. pneumonia were confirmed as blaNDM and one as OXA-48. For the purpose of controlling the spread of CRE in our institution, we recommend considering active surveillance cultures and screening patients transferred from other hospitals or coming from highly endemic settings at admission for these organisms. Keywords: Carbapenem-resistant, Enterobacteriaceae